The modern view of the idea of gamma-aminobutyric acid and its metabolite use to restore the motor function - А. G. Rodinskij; Т. V. Dемchenko; A. V. Моzgunov; К. V. Pysarevska (Patologìâ)
Aim. The literature review is devoted to the idea of using gamma-aminobutyric acid and its metabolites as medicines in conditions of peripheral nervous system injury. We examined the modern problems of denervated muscles restoration and a wide range of GABA effects which could be useful in conditions of injury. GABA and its metabolites have elements of nootropic, antihypoxic, organoprotective and anabolic activity. It is obvious that traumas of peripheral nerves lead to degeneration of injured fibers and significant disorders of metabolism at a number of regulatory levels. Regeneration of the nerve and the rate of recovery of muscle activity depend significantly on the level of resistivity of the injured nerve tissue and on possibilities for supply of this tissue by additional energetic reserves. Under the above-mentioned conditions, disorders are determined, to a significant extent, by the development of hypoxia. This is why elucidation of the phenomenology and mechanisms of action of GABA and its metabolites (agent are having, as was mentioned above, protective and antihypoxic properties) on the nerve/muscle apparatus and its links under conditions of traumatization of a large nerve is urgent. GABA and its metabolites have an antinociceptive activity which helps not only in inhibition of central and spinal neurons, but also helps to decrease pain sensitivity of patient after traumatic neuropathy to forming of motivation to recovery rehabilitation. Besides above mentioned, the ability of GABA to increase concentration of Ca2 + after injury was discussed. This ability may affect the expression of genes, the direction of the growth cone, and, perhaps, reduce cell death.